How voice shapes gender, self, and belonging for trans women - Moura, M. (18th Congress of the European Federation of Sexology, 2026)
Symposium of the Portuguese Society of Clinical Sexology (SPSC): Bridging Sexuality and Mental Wellness: A Symposium We will explore current knowledge on the relationship between voice and the psychosocial experience of trans women. Research shows how voice functions as a social marker and a central element of identity in the trans female population. Exposure to testosterone during puberty results in a voice that is perceived as masculine and may be incongruent with their gender identity. We will discuss how voice dysphoria and social perception inadequacy act as barriers to gender affirmation, while also exploring the effectiveness of clinical responses and the importance of multidisciplinary intervention for this population.